PECULIARITIES OF ARRANGEMENT OF RESEARCH AND INNOVATION ACTIVITIES IN MODERN TECHNICAL HIGHER EDUCATION INSTITUTION - Evgeny I. Yevtushenko; Yuliya V. Fomenko (Moscow Polytechnic University, 2016)
The article is devoted to the issues of organization of research and innovationactivities in modern technical higher education institution. The authors focus attention on involving students in research activities in order to provide reproduction of intellectual potential of the state by means of influx of young highly-qualified specialists into the various spheres of economy and scientific activities.